2023
DOI: 10.1590/2175-8239-jbn-2022-0030en
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of patients with chronic kidney disease on dialysis to pesticides

Abstract: Introduction: Pesticides can trigger kidney disease. Objective: To describe the exposure to pesticides of patients with chronic kidney disease on dialysis. Methods: Quantitative and descriptive field research, with 90 patients with chronic kidney disease on dialysis in two hemodialysis units in the state of Santa Catarina, through the application of a structured questionnaire. Participants were divided into two groups: with and without exposure to pesticides. The questionnaire was applied in hemodialysis cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Prolonged exposure to pesticides, even at low doses, can cause negative effects on human health, such as depression [ 12 ], it can cause endocrine and oxidative dysfunction, kidney disease, stress, problems in the immune and neurological systems, chromosomal alterations, among other effects that can be more serious in pregnant women and children [ 14 , 38 ], it can damage human DNA by influencing the immune system [ 39 ], and increase the risk of developing diabetes mellitus type 2 [ 25 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged exposure to pesticides, even at low doses, can cause negative effects on human health, such as depression [ 12 ], it can cause endocrine and oxidative dysfunction, kidney disease, stress, problems in the immune and neurological systems, chromosomal alterations, among other effects that can be more serious in pregnant women and children [ 14 , 38 ], it can damage human DNA by influencing the immune system [ 39 ], and increase the risk of developing diabetes mellitus type 2 [ 25 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, nearly 40% of pathological cases have been associated with environmental risk factors such as heavy metals, nanomaterials, and mostly agrochemical exposure (pesticides and fertilizers) [3]. Several studies have shown that various classes of pesticides can develop the main risk factors that cause chronic kidney illnesses [4]. Acephate, as an organophosphate insecticide, is considered to be the most frequently used pesticide in agriculture.…”
Section: Introductionmentioning
confidence: 99%